2019
DOI: 10.1016/j.cell.2019.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Basis of Mouse and Human Dendritic Cell Heterogeneity

Abstract: SummaryDendritic cells (DCs) play a critical role in orchestrating adaptive immune responses due to their unique ability to initiate T cell responses and direct their differentiation into effector lineages. Classical DCs have been divided into two subsets, cDC1 and cDC2, based on phenotypic markers and their distinct abilities to prime CD8 and CD4 T cells. While the transcriptional regulation of the cDC1 subset has been well characterized, cDC2 development and function remain poorly understood. By combining tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

50
546
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(599 citation statements)
references
References 98 publications
50
546
2
1
Order By: Relevance
“…The emergence of single-cell RNA sequencing (scRNA-seq) technologies has made it possible to compare high-throughput mouse and human datasets to search for translatable features. Previous scRNA-seq studies have attempted to characterize conserved cell types or states in mouse and human cells by measuring marker genes whose expression correlates with cellular function (Brown et al, 2019;Crinier et al, 2018;Yu et al, 2019;Zilionis et al, 2019). Standard clustering methods that partition cells into discrete groupings according to their transcriptional profile is fundamental to this analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of single-cell RNA sequencing (scRNA-seq) technologies has made it possible to compare high-throughput mouse and human datasets to search for translatable features. Previous scRNA-seq studies have attempted to characterize conserved cell types or states in mouse and human cells by measuring marker genes whose expression correlates with cellular function (Brown et al, 2019;Crinier et al, 2018;Yu et al, 2019;Zilionis et al, 2019). Standard clustering methods that partition cells into discrete groupings according to their transcriptional profile is fundamental to this analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The circulating CD14 + CD163 + cells represent the Inf DCs, whose proportion is correlated with disease activity index in SLE patients [44]. Brown et al identified two murine cDC2 subsets in spleen: pro-inflammatory RORγt + CLEC10A + CLEC12A + "cDC2B" resembling circulating DC2 in healthy subjects as well as colonic CD14 negative CD1c/ CLEC10A cluster in CD patients [31], and anti-inflammatory Tbet + "cDC2A", with the human counterpart detected in spleen and melanoma [53]. Because intestinal CD14 + CD163 − MNPs do not share synovial fluid Inf Mo-DCs or circulating Inf DCs gene signature and are unable to polarize naïve T cell differentiation [54], these cells are not fulfilling DC criteria.…”
Section: Mnps In Intestinal Mucosa During Inflammationmentioning
confidence: 99%
“…Since the discovery of DCs, they have been extensively studied in several contexts, from immunity to pathogens and tumors to the induction of tolerance or an immune response to transplants, to self, and more recently to microbi-ota and dietary antigens, with new discoveries happening constantly. Recent advances in the field have pointed at new DC function as well as new DC subsets with specific transcriptomes [4]. DCs are a heterogeneous group of cells that perform different functions in the immune response.…”
mentioning
confidence: 99%